2016
DOI: 10.1136/bmjopen-2015-010460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of conflict on medical education: a cross-sectional survey of students and institutions in Iraq

Abstract: ObjectiveThis study surveyed all Iraqi medical schools and a cross-section of Iraqi medical students regarding their institutional and student experiences of medical education amidst ongoing conflict. The objective was to better understand the current resources and challenges facing medical schools, and the impacts of conflict on the training landscape and student experience, to provide evidence for further research and policy development.SettingDeans of all Iraqi medical schools registered in the World Direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 34 publications
2
52
1
Order By: Relevance
“…Examples include lack of funds [57]), insufficient access to electronic resources [58], constrained availability of the internet [57,59] and sometimes, even war/conflicts [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Examples include lack of funds [57]), insufficient access to electronic resources [58], constrained availability of the internet [57,59] and sometimes, even war/conflicts [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Surveys of Iraqi physicians have found more than half of those who left the country did so for security reasons, while more than half of those remaining were seeking alternative employment or planning to leave the country soon, often citing similar concerns for their safety [ 10 , 11 ]. A recent survey found that the majority of medical students also plan to leave Iraq after graduation, but few studies have examined the underlying reasons [ 12 ]. A set of interviews with eight medical school deans and 197 students from various medical schools in Iraq found that the continuing conflict had a substantial effect on medical education and attitudes of medical students [ 12 ].…”
Section: Background and Rationalementioning
confidence: 99%
“…Despite the substantial burden of the disease, national surveillance programs for CE do not exist in Iraq. The fragile health services in Iraq, after years of international economic sanctions and ongoing political and ethnic conflicts, are challenging for any organized efforts to combat endemic tropical and zoonotic diseases (Barnett-Vanes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%